Percepções sobre a saúde bucal e o atendimento odontológico entre sujeitos em processo de transplante de células tronco hematopoiéticas - Suellen da Rocha Mendes (2016)
This study aimed to know and evaluate the perception about oral health and oral health care among patients submitted to hematopoietic stem cells transplantation. Semi-structured individual interviews were conducted with individuals in the post-transplant phase of hematopoietic stem cells, of both genders and over 18 years old that were undergoing treatment at dentistry school of Universidade Federal de Minas Gerais, between the second semester of 2014 and the first semester of 2015. All interviews were recorded and transcribed by a same researcher, maintaining the spelling and syntax used by respondents. The data analysis was based on content analysis and three topics were evaluated: what oral health is, why pre-transplant dental treatment was performed and the importance of dental treatment for the transplant of hematopoietic stem cells. Oral health is perceived as the act of taking care of teeth through oral hygiene procedures. The reason for the oral care involves regulatory requirements for transplantation, and when asked about the importance of dental treatment for transplant, interviewed focus on the prevention of infections during the period of low immunity. It is observed that individuals see dental treatment as a step to be followed before the transplant and that their main concern was not a better oral health but, instead to complete the treatment as soon as possible.